2014
DOI: 10.1016/j.pain.2014.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A3 adenosine receptor agonist prevents the development of paclitaxel-induced neuropathic pain by modulating spinal glial-restricted redox-dependent signaling pathways

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) accompanied by chronic neuropathic pain is the major dose-limiting toxicity of several anticancer agents including the taxane paclitaxel (Taxol®). A critical mechanism underlying paclitaxel-induced neuropathic pain is the increased production of peroxynitrite (PN) in spinal cord generated in response to activation of the superoxide-generating enzyme, NADPH oxidase. PN in turn contributes to the development of neuropathic pain by modulating several redox-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 61 publications
(113 reference statements)
4
93
0
Order By: Relevance
“…In particular it has been found that these effects were due to the inhibition of an astrocyte-associated neuroinflammatory 92 response in a model of oxaliplatin-induced peripheral neuropathy (Janes et al, 2014b). Furthermore A 3 AR agonists were found to prevent the development of paclitaxel-induced neuropathic pain by modulating spinal glial-restricted redox-dependent signaling pathways (Janes et al, 2014a). Importantly, the activation of A 3 AR in humans by potent, selective, and orally bioavailable A 3 AR agonists is not associated with cardiac or hemodynamic side effects at variance with A 1 and A 2A ARs and could represent a viable therapeutic strategy for chronic pain of distinct etiologies.…”
Section: Painmentioning
confidence: 99%
“…In particular it has been found that these effects were due to the inhibition of an astrocyte-associated neuroinflammatory 92 response in a model of oxaliplatin-induced peripheral neuropathy (Janes et al, 2014b). Furthermore A 3 AR agonists were found to prevent the development of paclitaxel-induced neuropathic pain by modulating spinal glial-restricted redox-dependent signaling pathways (Janes et al, 2014a). Importantly, the activation of A 3 AR in humans by potent, selective, and orally bioavailable A 3 AR agonists is not associated with cardiac or hemodynamic side effects at variance with A 1 and A 2A ARs and could represent a viable therapeutic strategy for chronic pain of distinct etiologies.…”
Section: Painmentioning
confidence: 99%
“…Endocannabinoids are broken down by fatty acid amide hydrolase (FAAH), and blocking this enzyme to increase endocannabinoid levels can reverse cold and mechanical sensitivity [43] and decrease C-fiber sensitization in a cisplatin model of CIPN [44]. Recently, translational research aimed at augmentation of signaling by A3 adenosine receptors has been suggested as an effective treatment for paclitaxel-related CIPN [45]. …”
Section: Neuronal Alterations Associated With Cipnmentioning
confidence: 99%
“…These conditions include physical and psychological stressful events like exercise, exposure to extreme thermal conditions, different kinds of pain, depression, sleep deprivation, hypoxia, etc. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In general, an increased IL-10 level during these events is associated with better outcome and adaptation.…”
Section: Physiological and Nonimmune Conditionsmentioning
confidence: 99%